The time of youth : work, social change, and politics in Africa. - Honwana, Alcinda (Kumarian Press Pub., 2012)
Most young Africans are living in waithood, a period of suspension between childhood and adulthood. Failed neo-liberal economic policies, bad governance and political instability have caused stable jobs to disappear without jobs that pay living wages, these young people cannot support families, thus becoming fully participating members of society. As this limbo becomes pervasive and prolonged, waithood in Africa becomes seemingly permanent, gradually replacing conventional adulthood. And with the deepening of the world economic crisis, youth in Europe, North America and other parts of the world face the same crisis of joblessness and restricted futures.In The Time of Youth, Alcinda Honwana examines the lives of young people in Africa, drawing on in-depth interviews in four countries: Mozambique, Senegal, South Africa and Tunisia. While the case studies are local to Africa, the book argues that the waithood generation is global, and possesses a tremendous transformative potential, as young people believe the struggle to overcome their predicament requires radical social and political change. From riots and protests in the streets of Maputo, Dakar, Madrid, London, New York and Santiago, to revolutions that overthrow dictatorships in Tunisia, Egypt and Libya, the waithood generation is taking upon itself to redress the wrongs of contemporary society and remake the world -- Présentation de l'éditeur.